The Comparative Survey of Life Quality in Renal Transplant Recipients, Peritoneal Dialysis, and Hemodialysis Patients in Kerman in the Year 2013 - Mehdi Amirkhani; Esmat Nouhi; Hassan Jamshidi (Fasa University of Medical Sciences, 2014)
Background & Objective: According to the World Health Organization (WHO) definition, quality of life is a state of complete physical, mental, and social health not merely the absence of the disease. End stage renal disease and its treatment affect patients' quality of life. Therefore, the present study surveyed the quality of life in renal transplant recipients, hemodialysis, and peritoneal dialysis patients in Kerman in the year 2012. The comparison was based on demographical information. Materials & Methods: This cross sectional study is an "analytical - comparison" one, which was conducted on 335 dialysis patients (150 hemodialysis patients, 95 renal transplant recipients, and 90 patients of peritoneal dialysis) in Hemodialysis , peritoneal dialysis, and nephrology wards of the educational hospitals of Kerman University of Medical Science in the year 2012. Results: The mean scores of life quality in hemodialysis patients, peritoneal dialysis patients, and renal transplant recipients were 44.97±13.53, 65.70±5.48, and 75.78 ± 6.68, respectively. There was a significant difference between these three groups. Conclusion: According to the results, the life quality of renal transplant recipients is better than other groups. Moreover, quality of life in hemodialysis patients was significantly lower than other groups.